Mood changes after watching pornography on the Internet are linked to tendencies towards Internet-pornography-viewing disorder. (June 2017) - Laier, Christian; Brand, Matthias
Abstract: Internet-pornography-viewing disorder (IPD) is considered one type of Internet-use disorder. For IPD's development, it was assumed theoretically that a dysfunctional use of Internet pornography to cope with depressive mood or stress might be considered to be a risk factor. To address the effect of Internet pornography use on mood, an online study with three measuring points with a sample of male participants was conducted. Participants were investigated regarding their tendencies towards IPD, personal use of Internet pornography, general mood, perceived stress, and their Internet pornography use motivation. Moreover, participants were asked regarding their current mood, sexual arousal, and need to masturbate before and after they watched Internet pornography self-determinedly in a private environment. Data showed that tendencies towards IPD were associated negatively with feeling generally good, awake, and calm and were correlated positively with perceived stress in daily life and using Internet pornography for excitation seeking and emotional avoidance. Self-determined use of Internet pornography in their private environment was accompanied by changes in mood and indicators of sexual arousal. Moreover, tendencies towards IPD were negatively related to mood before and after Internet-pornography use as well as an actual increase of good and calm mood. The results showed effects of watching Internet pornography on mood and sexual arousal which can be considered having reinforcing effects for the user. Thus, the results are in line with theoretical assumptions on IPD's development, in which the positive (and negative) reinforcement received by Internet-pornography use is related to cue-reactivity and craving reactions. Highlights: Investigation of mood and sexual arousal before and after self-determined Internet pornography use in private environment Watching pornography was associated to changes in mood and indicators of sexual arousal Current mood as well as changes in mood were associated to symptoms of Internet-pornography-viewing-disorder